Maxime Bôcher's concept of complementary philosophy of mathematics - Dadaczyński, Jerzy; Piechowicz, Robert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2020)
The main purpose of the present paper is to demonstrate that as early as 1904 pre-eminent American mathematician Maxime Bôcher was an adherent to the presently relevant argument of reasonableness, or even necessity of parallel development of two philosophical methods of reflection on mathematics, so that its essence could be more fully comprehended. The goal of the research gives rise to the question: what two types of philosophical deliberation on mathematics were proposed by Bôcher?
Keywords: philosophy; mathematics; Maxim Bôcher; metamathematics